Ultrafast carrier dynamics in GaN/InGaN multiple quantum wells nanorods - Chen, Weijian; Wen, Xiaoming; Latzel, Michael; Yang, Jianfeng; Huang, Shujuan; Shrestha, Santosh; Patterson, Robert; Christiansen, Silke; Conibeer, Gavin (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
GaN/InGaN multiple quantum wells (MQW) is a promising material for high-efficiency solid-state lighting. Ultrafast optical pump-probe spectroscopy is an important characterization technique for examining fundamental phenomena in semiconductor nanostructure with sub-picosecond resolution. In this study, ultrafast exciton and charge carrier dynamics in GaN/InGaN MQW planar layer and nanorod are investigated using femtosecond transient absorption (TA) techniques at room temperature. Here nanorods are fabricated by etching the GaN/InGaN MQW planar layers using nanosphere lithography and reactive ion etching. Photoluminescence efficiency of the nanorods have been proved to be much higher than that of the planar layers, but the mechanism of the nanorod structure improvement of PL efficiency is not adequately studied. By comparing the TA profile of the GaN/InGaN MQW planar layers and nanorods, the impact of surface states and nanorods lateral confinement in the ultrafast carrier dynamics of GaN/InGaN MQW is revealed. The nanorod sidewall surface states have a strong influence on the InGaN quantum well carrier dynamics. The ultrafast relaxation processes studied in this GaN/InGaN MQW nanostructure is essential for further optimization of device application.
CRIS-Team Scopus Importer:2023-03-07
Keywords: GaN; multiple quantum wells; nanorod; transient absorption; Ultrafast carrier dynamics